The Effective Using of Modern Multimodal Tools in Teaching of Chinese Language - Khotchenko , Iryna; Nikitina , Yuliia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The aim of this study is to investigate the effectiveness of modern multimodal means of teaching Chinese to students. It discusses the difficulties students face in mastering sounds, characters, grammar, pronunciation, vocabulary, and cultural aspects of the Chinese language. The relevance of the topic is due to the significant development of technology and the need to adapt educational methods to the needs of modern students. Taking into account the peculiarities of information perception with the help of the latest multimodal tools can significantly increase the effectiveness of teaching Chinese in higher education institutions. The article provides an analysis of the latest multimodal tools and outlines their effectiveness for different aspects of learning. The article provides an overview of multimodal tools such as Boom Cards, Quizlet, Baamboozle, LearningApps, Storybird, My storybook, Blooket, Kahoot, Wordwall, and Classtime. Examples of tasks that can be used to improve students’ Chinese language. The analysis of the study can help to create guidelines for the use of multimodal tools in teaching Chinese. Highlighting the most effective tools will allow them to be integrated into the curricula of universities, schools and language courses. The results of the study can serve as a basis for teachers to create seminars and workshops. The material will help prepare them for the effective use of multimodal tools. The use of multimodal tools in practice can significantly improve students’ skills in learning Chinese and, as a result, make language learning more interesting, memorable, diverse and effective.